Insights into the evolutionary history of an extinct South American freshwater snail based on historical DNA - Vogler, Roberto Eugenio (2016)
Fil: Vogler, Roberto Eugenio. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Instituto de Biología Subtropical. Instituto de Biología Subtropical. Nodo Posadas; Argentina.